PENGARUH KOMPETISI, CORPORATE GOVERNANCE, STRUKTUR KEPEMILIKAN TERHADAP PENGUNGKAPAN RISIKO - Cintia Heko Agustina; Dwi Ratmono (Diponegoro Journal of Accounting, 2014)
The purpose of this research is to provide empirical evidence of barriers to entry, ownership concentration, board size, board compotition, firm size, liquidity, industrial sector and auditor type. Barriers to entry was measured by total fixed assets, ownership concentration was measured by percentage of shares held by substantial shareholders >5%, board size was measured by number of board member, board compotition was measured by idependent board/total board, firm size was measured by log natural of net sales, liquidity was measured by the acid test rate, industrial sector and auditor type was measured by variabel dummy. Risk disclosure was measured by content analysis-sentence approach. The population of this research is 428 companies in the non-financial companies which were listed in Indonesian Stock Exchange (IDX). The research data were collected from annual report and financial statement for 2012. Based on stratified random sampling method, there are 102 samples. The reseacrh hypotesis were tested using multiple regression analysis. The results of this research show that barriers to entry and auditor type have significant relationships with risk disclosure. Next, variable ownership concentration, board size, board compotition, firm size, liquidity, industrial sector have no significant relationship with risk disclosure.